Prevalence of burnout in paediatric nurses: A systematic review and meta-analysis - Pradas-Hernandez, Laura; Ariza, Tania; Gómez-Urquiza, José Luis; Albendín-García, Luis; De la Fuente, Emilia I.; Cañadas-De la Fuente, Guillermo A. (Plos One, 2018)
Introduction Although burnout in paediatric nurses has been addressed in previous research, the heterogeneous nature of the results obtained and of the variables studied highlights the need for a detailed analysis of the literature. Objective The aim of this study was to analyse the literature on burnout characteristics, reported prevalence, severity and risk factors, to achieve a better understanding of the risk of emotional exhaustion, depersonalisation and feelings of low personal accomplishment. Method For this purpose, we carried out a systematic review and meta-analysis of the literature. The databases consulted were CINAHL, LILACS, PubMed, the Proquest Platform (Proquest Health & Medical Complete), Scielo and Scopus. This study used the search equation “burnout AND “pediatric nurs*””, and was conducted in July 2017. Results The search produced 34 studies targeting burnout in paediatric nurses, with no restrictions on the date of publication. Many of these studies detected moderate-high values for the three dimensions of burnout, and highlighted sociodemographic, psychological and job-related variables associated with this syndrome. The sample population for the meta-analysis was composed of 1600 paediatric nurses. The following prevalence values were obtained: (i) emotional exhaustion, 31% (95% CI: 25–37%); (ii) depersonalisation, 21% (95% CI: 11–33%); (iii) low personal accomplishment, 39% (95% CI: 28–50%). Conclusions A significant number of paediatric nurses were found to have moderate-high levels of emotional exhaustion and depersonalisation, and low levels of personal accomplishment. These nurses, therefore, were either experiencing burnout or at high risk of suffering it in the future. These results support the need for further study of the risk factors for burnout in paediatric nurses. They also highlight the importance of developing interventions or therapies to help prevent or attenuate the above symptoms, thus helping nurses cope with the workplace environment and with situations that may lead to burnout.
Keywords: job satisfaction; compassion fatigue; reliability generalization; emergency nurses; care nurses; stress; support; inventory; oncology; JCR; Scopus